1996
DOI: 10.1051/lait:1996427
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proteolysis and lipolysis in Serra cheese: effects of axial cheese location, ripening time and lactation season

Abstract: Summary -The degrees of proteolysis and Iipolysis in Serra cheese were measured in cheese samples obtained from experiments laid out as a three-way facto rial design replicated twice. The independent variables studied were the location within the cheese (from the center to the surface), the position in the lactation season (from October to June) and the ripening time (from 0 to 35 days). Ali three variables had statistically significant effects on the concentration of water soluble peptides (WSP), but only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…With the onset of ripening, both lipolysis and proteolysis occur, with an increase in the level of free fatty and amino-acids (Macedo et al, 1996). A negative correlation was observed between protein and lipid contents (ρ = -0.699, p = 0.015).…”
Section: Discussionmentioning
confidence: 94%
“…With the onset of ripening, both lipolysis and proteolysis occur, with an increase in the level of free fatty and amino-acids (Macedo et al, 1996). A negative correlation was observed between protein and lipid contents (ρ = -0.699, p = 0.015).…”
Section: Discussionmentioning
confidence: 94%
“…These higher levels of hydrophobic peptides may be due to the fact that the C. cardunculus proteinases hydrolyse bonds in hydrophobic areas. Macedo et al (1996) observed that C. cardunculus proteinases hydrolyse bonds in certain highly hydrophobic areas of bovine a s1 -casein (Ala 163 -Trp-Tyr-Tyr-Val 167 ) and b-casein (Ala 189 -Phe-Leu-Leu-Tyr 193 ), whereas chymosin cleaves only Trp 164 -Tyr 165 in this region of a s1 -casein and Ala in this region of b-casein. This fact is also confirmed by Gaya et al (1999) in their studies on Manchego cheese made using several types of coagulants.…”
Section: Hydrophobic/hydrophilic Peptide Ratiomentioning
confidence: 99%
“…Many studies have examined the influence of plant coagulant on the ripening of different varieties of Spanish and Portuguese cheese made from ewe's milk (Fernández-Salguero, Sanjuán, & Montero, 1991;Galán, Prados, Pino, Tejada, & Fernández-Salguero, 2008;Gaya, Carrera, Medina, & Núñez, 1999;Macedo, Costa, & Malcata, 1996). The effect of cyprosins on caprine casein has also been studied (Sousa & Malcata, 1997, 1998; however, there is very little information available about proteolysis in goats' milk cheese caused by these coagulants.…”
Section: Introductionmentioning
confidence: 99%
“…A number of raw ewes' milk cheeses from Portugal and Spain are produced using a crude aqueous extract (CAE) of Cynara cardunculus L. flowers as the coagulant Macedo, Costa, & Malcata, 1996). The acid aspartic proteinases extracted from cardoon flowers of various Cynara species, mainly C. cardunculus and, to a lesser degree, Cynara humilis , are referred to as cynarases or cyprosins and are characterized by their milk clotting activity.…”
Section: Introductionmentioning
confidence: 99%